A trianoni Magyarország törvényhatósági jogú városainak és megyeszékhelyeinek oktatási intézmény ellátottsága - Szabó, Attila (Közép-Európai Közlemények, 2010)
Having studied the supply of educational institutes of the towns with right of municipal authority we can see that the real borderline –contrary to our hypothesis –was not between the towns with right of municipal authority and county towns and villages, but between the settlements with and without higher educational institutes. Furthermore, we managed to support the evidence that the supply of educational institutes of a settlement was not determined by the legal state of the given settlement, but the demand and potential of the inhabitants, moreover, in case of religious education, it was dominated exclusively by denominational issues. Examining the supply of educational institutes in towns that became county seats after the Treaty of Trianon, we experienced that as these towns could not show significant social-economic progress parallel with or prior to their administrative advance, the lack of this progress – irrespectively of their position gained in the administration – restrained their educational state (on the level of the dualistic era).